Elementary School Teachers' Acceptance of the Digital Media Canva Site in Deep Learning-Based Instruction: A Study Using the UTAUT Model - Herma Susanah; Yunus Abidin; Dede Tri Kurniawan; Dede Margo (Sekolah Dasar: Kajian Teori dan Praktik Pendidikan, 2025)
Abstract: The world of education is required to continue to innovate, including in the way teachers compile teaching materials that are interesting and relevant to students. One of the main challenges is how teachers can accept and utilize new technology optimally in teaching and learning activities. The study aimed to find out the extent to which elementary school teachers accept the use of Canva to create deep learning-based teaching materials, which encourage students' deep understanding. Using a quantitative approach, this study involved 149 elementary school teachers in the city of Bandung as respondents. An instrument in the form of a questionnaire was developed based on the UTAUT framework, and the data were analyzed by linear regression. The results show that performance expectations, ease of use, social influence, and availability of technical support all play an important role in shaping teachers' intentions to use Canva. These findings show that teachers respond positively to this technology and see it as an effective tool in developing more meaningful learning. In conclusion, successful adoption of technologies like Canva requires real support in the form of training, tools, and school policies that encourage innovation in the classroom. Abstrak: Di era digital saat ini, dunia pendidikan dituntut untuk terus berinovasi, termasuk dalam cara guru menyusun bahan ajar yang menarik dan relevan bagi siswa. Salah satu tantangan utama adalah bagaimana guru dapat menerima dan memanfaatkan teknologi baru secara optimal dalam kegiatan belajar mengajar. Penelitian ini bertujuan untuk mengetahui sejauh mana guru sekolah dasar menerima penggunaan Canva untuk membuat bahan ajar berbasis deep learning, yang mendorong pemahaman mendalam siswa. Menggunakan pendekatan kuantitatif, penelitian ini melibatkan 149 guru SD di Kota Bandung sebagai responden. Instrumen berupa kuesioner dikembangkan berdasarkan kerangka UTAUT, dan data dianalisis dengan regresi linear. Hasilnya menunjukkan bahwa ekspektasi kinerja, kemudahan penggunaan, pengaruh sosial, serta ketersediaan dukungan teknis semuanya berperan penting dalam membentuk niat guru menggunakan Canva. Temuan ini menunjukkan bahwa guru merespons positif teknologi ini dan melihatnya sebagai alat bantu yang efektif dalam mengembangkan pembelajaran yang lebih bermakna. Kesimpulannya, keberhasilan adopsi teknologi seperti Canva membutuhkan dukungan nyata berupa pelatihan, sarana, dan kebijakan sekolah yang mendorong inovasi di ruang kelas.